Analysis of Motion and Internal Loading in Redundantly Actuated Human Eyeball - Jungkyu Kim; Abid Imran; Byung-Ju Yi (IEEE Access, 2020)
The 3-DOF rotational motion of the human eyeball is created by using six extraocular muscles. For the force-redundant system of the human eyeball, a load distribution algorithm is proposed to investigate the dynamics and intrinsic load distribution of the eyeball. Initially, the role of each extraocular muscle is explained by describing the anatomy of the human eye. Furthermore, activity of each muscle group is analyzed to create six primitive motions of the human eye. Moreover, the dynamic model of the human eye is developed to simulate the human eye motion. Finally, a load distribution algorithm is newly developed and it is found that asymmetric arrangement of six extraocular muscles with respect to the eye axis enables the human eye not only to create the motion using minimum number of extraocular muscles, but also to ensure stability in other directions by providing antagonistic internal loading. Surprisingly, it is also found that all six primitive motions of the eyeball require three independent muscles, which is different from clinical observation so far.